Association of Low-Density Lipoprotein Receptor (LDLR) Arg471Gly with Increased Homocysteine Level among the Iban Ethnic Group in the Sarawak Population - Mohd Aminudin, Bin Mustapha; Sim, Sai-Peng; Hafizah Hanis, Hood; Siaw, Yun Ted; Goh, Maybelline Boon Ling; Helmy, Hazmi (Japan International Cultural Exchange Foundation (JICEF), 2019)
Objective: To determine the polymorphic allele and genotype frequencies of LDLR Arg471Gly. It is aimed to elucidate the association of the polymorphic allele and genotypes with clinical profiles such as total cholesterol (TC), high- density lipoprotein (HDL), low- density lipoprotein (LDL) and homocysteine level in the Iban ethnic group in Sarawak. Material and methods: One hundred and fourteen (114) individuals of the Iban ethnic group were recruited as the study subjects. The Allele Specific PCR (AS-PCR) was used in the genotyping. Association for genotype frequencies and clinical profile was calculated using One Way ANOVA. As for the association of allele frequencies and clinical profile Independent Sample T test was used. Results: Allele and genotype frequency association with homocysteine level showed statistically significant difference with p value less than 0.05. The wildtype and variant genotypes of LDLR Arg471Gly shows significant association with high homocysteine level with F (2,112) = 7.048, p < 0.05. Similarly, the variant allele of LDLR Arg471Gly is significantly associated with high level of homocysteine with t(2.267), p value of 0.024. Conclusion: Our results showed that the genetic diversity of LDLR gene influences the susceptibility to increased level of homocysteine in the Malaysian population and support the involvement of LDLR mediated pathways in the process of familial hypercholesterolemia (FH).